Implementasi Program Imtaq Bagi Anak Usia Dini Di TK Negeri Pembina - Eko Nursalim; Tiara Sarawati; Putri Zarifah; Chairunnisa Nahda; Thaibatul Islamiyah (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
This study aims to discuss the implementation of the Imtaq program as a strategy to improve character education at TK Negeri Pembina Sangatta. Education plays an important role in shaping individual character in accordance with prevailing social and cultural norms. Character education aims to increase faith, devotion, and noble character. This research adopts a qualitative approach that focuses on understanding and interpreting the technique through the methods of interview, observation, and document analysis. The research findings indicate that: (1) The planning of Imtaq program in TK Negeri Pembina Sangatta involves the identification of goals, learners, curriculum, learning methods, time, schedule, evaluation, and participation of parents and community. (2) Implementation of the Imtaq program focuses on moral education and includes Quranic activities, dhuha prayers, introduction of hijaiyah letters, memorization of short surahs, and other activities that support the development of character and morals of early childhood. The research data shows the success of the IMTAQ program in achieving the goals of character education, where the IMTAQ program has the main objective of improving the quality of students' faith and piety.